Knowledge sharing within virtual teams in Kedah / Perlis IRBM / Hafiz Abu Hassan and Mohd Huzaimie Ahmad Kafrawi - Abu Hassan, Hafiz; Ahmad Kafrawi, Mohd Huzaimie (2016)
This study examined factors that might impact staffs knowledge sharing within virtual teams in IRBM. These factors included: trust, mutual influence, conflict, leadership, and cohesion. The question are adopted from JinXia He, 2009. Correlation design was conducted to discover if there are any relationships among these five factors and knowledge sharing within virtual teams. Participants in this study were 150 staffs of Kedah/Perlis IRBM. The study conducted at Kedah/Perlis Inland Revenue Board Malaysia (IRBM) consists Kedah/Perlis States Directors Office, Alor Setar branch, Kangar branch, Sungai Petani branch and Alor Setar Investigation branch. The results indicate that trust and leadership had strong direct relationships with knowledge sharing. Meanwhile conflict and team unity had negative relationship with knowledge sharing in this study.